Life during the Russian revolution - Sherrow, Victoria (San Diego, CA : Lucent Books, 1998)
Discusses the background, historical context, events, and way of life of the Russian Revolution.
Includes bibliographical references (p. 86-90) and index.
Keywords: Soviet Union -- History -- Revolution, 1917-1921 -- Juvenile literature; Soviet Union -- History -- Revolution, 1917-1921.